Pembuatan Video Live Stream Dengan OBS Studio Untuk Mendukung Pembelajaran Hybrid - Santy Handayani; Didik Nur Huda (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Physics learning at high school level during the COVID-19 pandemic was carried out in a hybrid manner, namely a combination of face-to-face and online, resulting in teaching staff experiencing changes in teaching methods. Change from completely online to partly online (live streaming) and face to face in class. This hybrid learning needs to be done with the OBS Studio application for live streaming. Classroom learning uses OBS Studio and record the screen so it can be read well on live streaming.